Recent changes in the features of hypertrophic pyloric stenosis. Issue 5 (3rd February 2016) - Bakal, Unal; Sarac, Mehmet; Aydin, Mustafa; Tartar, Tugay; Kazez, Ahmet
Abstract: Background: Hypertrophic pyloric stenosis (HPS) is a rare cause of non‐bilious vomiting in young infants; the condition requires surgical management. Diagnosis is based on clinical, laboratory, and radiological findings. In the present study, we evaluate recent changes in the features of HPS. Method: We retrospectively reviewed the demographic, clinical, and laboratory data on 56 HPS patients who underwent pyloromyotomy between 1996 and 2015. Patients were divided into two groups according to date of operation (group 1, 1996–2006; group 2, 2007–2015). Results: Group 1 consisted of 30 patients and group 2, 26. The age at diagnosis was longer in group 2 (43.3 ± 13.1 days) than group 1 (37.4 ± 17.7 days). All diagnoses were confirmed on ultrasonography. Pyloromyotomy was performed on all 56 patients (48 boys, 8 girls). Significant between‐group differences were evident in terms of age at onset of vomiting; rate of dehydration; development of palpable olive‐shaped abdominal mass; serum urea and creatinine; acid–base status; and air distribution pattern on abdominal radiography (all P  < 0.05). Conclusion: The frequency of olive‐shaped abdominal mass evident on physical examination decreased significantly over time, and was lower than published values. Early diagnosis triggers timely support and surgical intervention, and may thus prevent development of the classical clinical and laboratory findings of late‐stage HPS. The remarkable recent advances in ultrasonography and techniques allow HPS to be diagnosed earlier than formerly.